Nanomechanical properties of glass-ceramic films obtained by pressure impregnation of oxide powders on commercial float glass surfaces - Cava, S.; Sequinel, T.; Tebcherani, S. M.; Michel, M. D.; Lepienski, C. M.; Varela, José Arana [UNESP] (Elsevier B.V., 2010)
The fracture toughness, hardness and elastic modulus of thin films prepared by high air pressure impregnation of SnO(2) nanoparticles on glass surfaces were measured using indentation techniques. The films were produced by two SnO(2) synthesis routes, at varying temperatures and constant pressure and time. The fracture toughness of the films was measured by the length of radial cracks determined by Vickers indentation. The hardness and elastic modulus were measured by the nanoindentation technique using a Berkovich tip. The mechanical properties of the surfaces modified with SnO(2) nanoparticles showed changes when compared with the mechanical properties of unmodified alkaline glass. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Glass ceramics; Hardness; Indentation, microindentation; Strength; Optical microscopy; Scanning electron microscopy; Nanoparticles; Soda-lime-silica; Solution chemistry; Tin oxide